Comics, Adoptionen oder doch das Original? – Goethes Faust im kompetenzorientierten Deutschunterricht. - Kuzminykh, Ksenia (Glottodidactica, 2015)
Goethe’s Faust was long defined in Germany as an established part of literature lessons and as a part of canon, but a paradigm change in didactics and in literature science has challenged both. This essay takes a brief look at history of German-literature-lessons and at different methods of teaching and reading literature, especially Goethe’s Faust – analytical, productive and creative. It gives a survey about children’s books to Faust, comics and summaries and demonstrates the correlation between knowledge and reading comprehension.